Validation of an off-road cognitive and behavioral evaluation protocol for driving after a stroke - Laffarga-Gómez, L.; Szot, A.C.; Castro, C.; Espinosa-García, M.; Funes, M.J.; Rodríguez-Bailón, María (Elsevier, 2026)
Objective: People who have experienced a stroke may exhibit neuropsychological and behavioral impairments that affect their ability to drive safely. To our knowledge, there is currently no standardized, validated assessment protocol for this purpose in the Spanish context. Conse- quently, the aim of this research was to validate a protocol to address this need. Methods: We conducted a comprehensive cognitive and behavioral assessment in a group of people with stroke. Different correlation analyses were carried out between the variables and the on-road score, as well as a linear regression analysis. Subsequently, serial trichotomization was performed. Results: 45 people with stroke were evaluated. Several variables of bimanual coordination and motor planning, divided attention, visuospatial skills, executive functions, hazard prediction and dissociative driving style were related to the on-road score. The linear regression model, including the variables that correlated moderately, explained 71.8% of the on-road score (p = 0.014). Serial trichotomization with 4 tests (visual perception, divided attention, bimanual coordination, and hazard prediction) classified 22.72% of participants as fit and 2.72% as unfit. Impact: This study pioneers the validation of an off-road assessment protocol that measures the ability to drive safely in Spanish individuals who have suffered a stroke. The results help in clinical decision-making to reduce evaluation times and to work on possible rehabilitation of altered cognitive processes to return to driving. ClinicalTrials.gov: This study is part of the project registered under NCT 05659667.
Keywords: Automovilistas; Neuropsicología; Terapia ocupacional; Fitness to drive; Neuropsychological assessment; Occupational therapy